(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Lupeol (1) and Stigmasterol (2) were isolated from the crude extracts of the stem bark of Citrus macroptera (Family: Rutaceae) for the first time. The n-hexane, dichloromethane and methanol extracts were screened in vitro for antioxidant activity using the 1, 1-diphenyl-2-picrylhydrazyl-hydrate (DPPH) free radical scavenging assay. The hot methanol extract showed potential antioxidant activity (IC50: 178.96 Î¼g/ml) whereas the cold methanol and dichloromethane extracts showed moderate activity (IC50: 242.78 Î¼g/ml and 255.78 Î¼g/ml respectively). Mild antioxidant activity was observed with the n-hexane extract of the stem bark of Citrus macroptera (IC50: 422.94 Î¼g/ml). Key words: Citrus macroptera, Rutaceae, Lupeol, Stigmasterol, Antioxidant. Â doi: 10.3329/bjsir.v43i4.2235 Bangladesh J. Sci. Ind. Res. 43(4), 449-454, 2008